2017
DOI: 10.1111/ppe.12348
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after Inpatient Treatment for Severe Pneumonia in Children: a Cohort Study

Abstract: BackgroundAlthough pneumonia is a leading cause of inpatient mortality, deaths may also occur after discharge from hospital. However, prior studies have been small, in selected groups or did not fully evaluate risk factors, particularly malnutrition and HIV. We determined 1‐year post‐discharge mortality and risk factors among children diagnosed with severe pneumonia.MethodsA cohort study of children aged 1–59 months admitted to Kilifi County Hospital with severe pneumonia (2007–12). The primary outcome was dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 29 publications
4
51
1
1
Order By: Relevance
“…There were more admissions and deaths in children aged 5–9 years, but there was higher case fatality among those aged 10–14 years (14.1%). Pneumonia case fatality rates (CFRs) have not been reported before in these age groups and, perhaps surprisingly they are similar to those reported in hospital-based pneumonia studies of children under 5 years: studies from sub-Saharan Africa report rates ranging from 5% to 10.4% 18 21–25. These include pneumonia mortality rates from studies within the CIN: for children aged between 2 and 59 months one study reported CFR of 5.9%,21 and another reported 5%, the latter excluded children with severe acute malnutrition, meningitis and HIV 18…”
Section: Discussionsupporting
confidence: 59%
“…There were more admissions and deaths in children aged 5–9 years, but there was higher case fatality among those aged 10–14 years (14.1%). Pneumonia case fatality rates (CFRs) have not been reported before in these age groups and, perhaps surprisingly they are similar to those reported in hospital-based pneumonia studies of children under 5 years: studies from sub-Saharan Africa report rates ranging from 5% to 10.4% 18 21–25. These include pneumonia mortality rates from studies within the CIN: for children aged between 2 and 59 months one study reported CFR of 5.9%,21 and another reported 5%, the latter excluded children with severe acute malnutrition, meningitis and HIV 18…”
Section: Discussionsupporting
confidence: 59%
“…Current guidelines recommend that children admitted with cSAM are discharged and transferred to community care when their medical complications, including oedema, are resolving, they are clinically well and alert, and have good appetite, rather than hospital discharge being based on anthropometric criteria (WHO, 2019). However, children with cSAM experience a high rate of mortality and readmission in the months following hospital discharge especially in sub-Saharan Africa (Berkley et al, 2016;Chhibber et al, 2015;Dubray et al, 2008;Kerac et al, 2009;Moisi et al, 2011;Ngari et al, 2017;Trehan et al, 2013;Veirum, Sodeman, Biai, Hedegård, & Aaby, 2007;Wiens et al, 2013;Wiens et al, 2015). Recent systematic reviews reported paediatric post-discharge mortality rates in resource-poor countries of up to 18% that may exceed in-hospital mortality rates in many settings (Nemetchek et al, 2018;Wiens et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The WHZ was calculated using the 2006 WHO child growth standards [16]. The weight of the children during admission was done using an electronic scale (Seca, Birmingham, UK) that has a weekly check for consistency [5,17]. The heights of the children were measured with a stadiometer (Seca 215, Birmingham, UK) [18] except for children with less than 2 years and those who could not stand whose length was measured using a standard calibrated board.…”
Section: Outcome and Explanatory Variablesmentioning
confidence: 99%